Polarized actin and VE-cadherin dynamics regulate junctional remodelling and cell migration during sprouting angiogenesis - Cao, Jiahui; Ehling, Manuel; März, Sigrid; Seebach, Jochen; Tarbashevich, Katsiaryna; Sixta, Tomas; Pitulescu, Mara E; Werner, Ann-Cathrin; Flach, Boris; Montanez, Eloi; Raz, Erez; Adams, Ralf H; et al. (Nature communications, 2017)
VEGFR-2/Notch signalling regulates angiogenesis in part by driving the remodelling of endothelial cell junctions and by inducing cell migration. Here, we show that VEGF-induced polarized cell elongation increases cell perimeter and decreases the relative VE-cadherin concentration at junctions, triggering polarized formation of actin-driven junction-associated intermittent lamellipodia (JAIL) under control of the WASP/WAVE/ARP2/3 complex. JAIL allow formation of new VE-cadherin adhesion sites that are critical for cell migration and monolayer integrity. Whereas at the leading edge of the cell, large JAIL drive cell migration with supportive contraction, lateral junctions show small JAIL that allow relative cell movement. VEGFR-2 activation initiates cell elongation through dephosphorylation of junctional myosin light chain II, which leads to a local loss of tension to induce JAIL-mediated junctional remodelling. These events require both microtubules and polarized Rac activity. Together, we propose a model where polarized JAIL formation drives directed cell migration and junctional remodelling during sprouting angiogenesis.
Keywords: Actin-Related Protein 2-3 Complex; signální transdukce; Cadherins; Cell Adhesion; modely kardiovaskulární; remodelace cév; Models, Cardiovascular; Intercellular Junctions; Neovascularization, Physiologic; Wiskott-Aldrich Syndrome Protein Family; Cell Movement; Myosin Light Chains; Endothelial Cells; rodina proteinů Wiskottova-Aldrichova syndromu; rac GTP-Binding Proteins; Humans; lidé; protein Wiskottova-Aldrichova syndromu; lehké řetězce myosinu; Cell Polarity; Microtubules; aktiny; Actin-Related Protein 2; Vascular Endothelial Growth Factor Receptor-2; Cardiac Myosins; srdeční myosiny; Wiskott-Aldrich Syndrome Protein; fyziologická neovaskularizace; Actin-Related Protein 3; mikrotubuly; Endothelium, Vascular; mezibuněčné spoje; pohyb buněk; protein 2 související s aktinem; komplex proteinů 2-3 souvisejících s aktinem; buněčná adheze; kadheriny; pseudopodia; protein 3 související s aktinem; Antigens, CD; cévní endotel; endoteliální buňky pupečníkové žíly (lidské); vaskulární endoteliální růstový faktor A; CD antigeny; Human Umbilical Vein Endothelial Cells; Signal Transduction; Actins; Vascular Endothelial Growth Factor A; endoteliální buňky; receptor 2 pro vaskulární endoteliální růstový faktor; polarita buněk; rac proteiny vázající GTP; Vascular Remodeling; Pseudopodia